Hypnosis Increases Heat Detection and Heat Pain Thresholds in Healthy Volunteers. Issue 1 (1st January 2002) - Langlade, Agnès; Jussiau, Claire; Lamonerie, Laurent; Marret, Emmanuel; Bonnet, Francis
Abstract : Background and Objectives: Hypnosis has been reported to induce analgesia and to facilitate anesthesia. To date, hypnotic-induced analgesia has had little explanation and it has even been questioned. The current study was thus designed to investigate the effect of hypnotic suggestion on thermal-detection thresholds, heat pain, and heat-pain tolerance thresholds. Methods: In 15 healthy volunteers, enrolled in a randomized cross-over study, thermal thresholds were investigated in 2 sequences of measurements, under waking and hypnotic states, using a thermal stimulator. Results: Heat detection and heat-pain thresholds were increased under hypnosis (from 34.3 ± .9°C to 36.0 ± 2.9°C and 45.0 ± 3.7°C to 46.7 ± 2.7°C, respectively, P < .05), whereas heat-pain tolerance and cold-detection thresholds were not statistically changed. Conclusion: These results indicate that hypnosis may partly impair the detection of Aδ and C fibers stimulation, potentially explaining its analgesic effect.